Lavandula Stoechas Extract Incorporated Polylactic Acid Nanofibrous Mats as an Antibacterial and Cytocompatible Wound Dressing - Mutlu, Betül; Çiftçi, Fatih; Üstündağ, Cem Bülent; Koç, Rabia Çakır (Elsevier, 2023)
In recent years, great efforts have been devoted to the design and production of bioactive wound dressings that promote skin regeneration and prevent infection. Many plant extracts and essential oils have been widely accepted in traditional medicine for a wide variety of medicinal purposes, especially wound healing. Over the past decade, many studies have focused on manufacturing and designing wound dressings containing plant compounds and extracts. In this study, Lavandula stoechas extract (LSE) (0.25 %, 0.5 %, and 1%wt) incorporatedpolylactic acid (PLA) nanofibrous mats were successfully produced and characterized. Microstructural analysis by SEM revealed that the fiber diameter changed with the increase in the amount of LSE. Also, the nanofibrous mats were evaluated for their in vitro antibacterial, cytotoxicity, and wound healing properties for their use as a wound dressing material. According to the results of the disc diffusion test, PLA nanofibrous mats containing LSE %1 showed 9.65 ± 0.46 and 7.37 ± 0.03 inhibition zone (mm) against E. coli and S. aureus, respectively. According to the results of the in vitro wound healing assay, mats containing 0.5 % LSE showed better-wound closure activity compared to the control. Our results show that LSE-incorporated nanofibrous dressings can be an effective alternative with good antimicrobial activity.
Keywords: Lavandula Stoechas; Polylactic Acid; Bioactive Wound Dressing; Nanofibrous